The intergenerational effect of parental health shocks on adult children fertility decisions in China - Shouwei Qi; Xiang Li; Kent Matthews (Cardiff University, Cardiff Business School, 2024)
We investigate the intergenerational effect of parental health shocks on the fertility choices of adult children in China. By using a comprehensive longitudinal dataset of Chinese households, severe and unexpected health shocks to parents have been identified. To address sample imbalance issues in survey data and endogeneity concerns characteristic of traditional health shock studies, we employ two matching methodologies: Coarsened Exact Matching (CEM) and Propensity Score Matching (PSM). Our findings indicate that parental health shocks significantly postpone the reproductive age of adult children and reduce their likelihood of having more children than they originally planned. We also find persistent differences in fertility decisions for the first, second and third child among adult children. The economic constraints inferred from this study have notable implications on the reduced fertility behavior of adult children, thereby affecting their entire reproductive life cycle.
Keywords: D01; D31; I12; 13; J18; 330; parental health shocks; fertility decisions; intergenerational effect